Pengaruh Perputaran Kas Dan Perputaran Piutang Terhadap Sisa Hasil Usaha Pada Unit Usaha Simpan Pinjam Koperasi Karyawan PDAM Tirta Mahakam Di Tenggarong - Nugraha, Muhammad Bhakti; Jais, Achmad; Hermanto, Muhammad (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2018)
Abstract:The purpose of this research is to know whether there is a significant influence of cash turnover anda receivable turnover to the rest of business result (SHU) and to analyze the dominant influence to the rest of business result (SHU) on Employee Cooperative PDAM Tirta Mahakam In Tenggarong. The data used in this research is the financial report Employee Cooperation PDAM Tirta Mahakam namely profit and loss and balance sheet 2012-2016 period. Analyzer used is multiple regression analysis, correlation coefficient analysis and coefficient of determination, t test and test f. The hypothesis is There is influence of cash turnover and receivable turnover to the rest of business result (SHU) on Unit Business Saving and Loan Employee Cooperative Unit of PDAM Tirta Mahakam In Tenggarong and Variable receivable turnover have the ost dominant influence to the rest of business result (SHU) on Unit Business Savings and Loan Employee Cooperative Unit of PDAM Tirta Mahakam In Tenggarong.The result of research shows that simultaneously cash turnover variabels and receivableturnover no effect on SHU on unit business saving and loan Employee Cooperative PDAM Tirta Mahakam In Tenggarong where the value of F arithmetic = 5,386 < F table = 19,000. The value of t test receivable turnover (X2) is 0,182 when compared with the test value of t cash turnover (X1) 0f 3,207 then cash turnover has an dominant influence on the rest of of business result.The number of R Square generated is 0,843, it shows that 84,3% of the remaining business result is influenced by cash turnover and receivable turnover. While the remaining 15,7% influenced by other factors or other variables beyond this study. Keyword: cash turnover, account receivable turnover, rest of business resultÂ